Comparison of Planar (ISFET) And Extended Gate Field-Effect Transistors (EGFET) for Biosensor Applications by Varying The Length of The Sensing Area To Improve Drain Current (Journal of Pharmaceutical Negative Results, 2022)
Aim: The present research aims to simulate and compare the drain current of Ion Selective Field Effect Transistor (ISFET) and Extended Gate Field Effect Transistor (EGFET) for biosensor application by varying the length of the sensing area from 1µm to 0.0001cm and by keeping the other parameters as constant.Materials and Methods: Two nano biosensors were analyzed in which ISFET (N=20) was the sensing element in one biosensor and EGFET (N=20) was the sensing element in the second biosensor. The total number of samples for the two groups is 40, twenty each, and simulated using a nanoHUB simulation tool with a G-power of 80%.Results: From the nanoHUB simulation tool, the drain current for both the ISFET and EGFET were analyzed. The simulation results obtained from the biosensor provide the conductance with a significant drain current. The study has a significance value of p<0.05 i.e, (p=0.006) for hybridized mode and (p=0.009) for unhybridized mode. The ISFET gives a higher drain current (1.82574E-9mA, p<0.05) than EGFET (8.52684E-10mA, p<0.05).Conclusion: ISFET based nano biosensors show significantly higher performance than EGFET nano biosensors.